Gerakan Rimpang dan Kapasitas Refleksif Kaum Muda di Tengah Kemunduran Demokrasi Indonesia - Pusairi; Hasugian, Alif (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2026)
This article aims to analyse how social change has contributed to the emergence of the rhizomatic movement as a form of contemporary youth activism. The stagnation of the leftist movement due to its history of disorganisation and the crisis of democracy caused by the rise of authoritarian regimes pose a real threat to the lives of young people and social movements in Indonesia. Therefore, the rhizomatic movement, which is synonymous with fluid and leaderless activism, has become an alternative channel for young people to express their reflexive biographies amid the crisis of democracy and uncertainty about the future. Through a qualitative approach based on literature review, this article attempts to examine in depth the academic literature related to the issues of rhizomatic movements, youth activism, and democratic decline in Indonesia. The results of the study show that rhizomatic movements function as a space for the expression of youth reflexivity in responding to socio-political uncertainty and the democratic crisis, especially through digital movement space and solidarity in various regions. However, these dynamics also face structural obstacles in the form of surveillance in the digital space, fragmentation of movements, and limitations in institutionalisation that affect the sustainability of the agenda for change.